Detrimental effects of Bartonella henselae are counteracted by l-arginine and nitric oxide in human endothelial progenitor cells - Salvatore, Paola (National Academy of Sciences, 2008)
The recruitment of circulating endothelial progenitor cells (EPCs) might have a beneficial effect on the clinical course of several diseases. Endothelial damage and detachment of endothelial cells are known to occur in infection, tissue ischemia, and sepsis. These detrimental effects in EPCs are unknown. Here we elucidated whether human EPCs internalize Bartonella henselae constituting a circulating niche of the pathogen. B. henselae invades EPCs as shown by gentamicin protection assays and transmission electron microscopy (TEM). Dil-Ac-LDL/lectin double immunostaining and fluorescence-activated cell sorting (FACS) analysis of EPCs revealed EPC bioactivity after infection with B. henselae. Nitric oxide (NO) and its precursor l-arginine (l-arg) exert a plethora of beneficial effects on vascular function and modulation of immune response. Therefore, we tested also the hypothesis that l-arg (1–30 mM) would affect the infection of B. henselae or tumor necrosis factor (TNF) in EPCs. Our data provide evidence that l-arg counteracts detrimental effects induced by TNF or Bartonella infections via NO (confirmed by DETA-NO and L-NMMA experiments) and by modulation of p38 kinase phosphorylation. Microarray analysis indicated several genes involved in immune response were differentially expressed in Bartonella-infected EPCs, whereas these genes returned in steady state when cells were exposed to sustained doses of l-arg. This mechanism may have broad therapeutic applications in tissue ischemia, angiogenesis, immune response, and sepsis.